Evaluasi Kinerja Guru SMA Negeri 27 Kabupaten Seram Bagian Barat - La Musa; R. Kempa; A. Sahalessy; Sumarni Rumfot (LP. Ma'arif Janggan Magetan, 2024)
The objectives of this research are 1) Evaluate the performance of teachers at Senior High School 27 West Seram Regency in the aspect of pedagogical competence. 2) Evaluate the performance of teachers at Senior High School 27 West Seram Regency in the aspect of personality competency. 3) Evaluate the performance of teachers at Senior High School 27 West Seram Regency in the aspect of social competence. This research is evaluation research using a qualitative descriptive approach, namely research that aims to describe the situation comprehensively in its actual context. In this case, to collect information about teacher competency evaluations at Senior High School 27 West Seram Regency then use this information as a basis or foundation for making policies or decisions about quality school programs. In this research, the research design developed is a teacher competency evaluation model design for Senior High School 27 West Seram Regency using the Stake model. This model emphasizes the implementation of two main things, namely: (a) description and (b) judgments. Data collection was carried out using observation, interviews and documentation studies. The data analysis components used in this research are data reduction, data presentation, and data verification. The results of this research showed that teaching and learning activities are the main activities that teachers always carry out at Senior High School 27 West Seram Regency. Schools are given the freedom to choose effective learning and teaching strategies, methods and techniques, according to the characteristics of subjects, students, teachers and the real conditions of resources available at the school. Learning planning begins with mapping basic competencies and indicators, preparing the syllabus, preparing lesson plans, preparing the annual program, preparing the semester program, and then the result of the planning is a pattern regarding the teaching program that will be used in the learning process in the classroom, and in connection with 4 competencies that a teacher must have, namely; pedagogical competence, professional competence, personality competence and social competence. Basically, teachers at Senior High School 27 West Seram Regency have pedagogical, professional, personal and social competencies.